A political–economic explanation of "internet space". Issue 1 (3rd August 2020) - Ma, Yan; Minqiang, Cai; Yun, Li
Abstract : Purpose: The purpose of this paper is to define the Internet as a virtual space supported by technologies and presented in the form of socioeconomic relations from the perspective of political economy. The Internet space is a unique virtual commodity different from ordinary commodities and has the following effect characteristics: super replicability, space- and time-transcendence, open-source shareability and reality–virtuality transformation. Design/methodology/approach: Internet space can also be imagined as a piece of virtual land. Internet space can be deemed as a piece of virtual land and its value can be divided into labor value and virtual value. The pricing model of virtual value is mainly determined by the gain and discount rate and this value comes from the transfer and markup of social value. In the context of the Internet Plus era, Internet space has become an essential economic factor that influences human economic activities. Findings: Therefore, it is of practical significance and theoretical value to introduce Internet space as an economic variable into the framework of economic theory. The realistic logic of Internet space is to influence human economic behaviors with the combination of information binding. Originality/value: The theoretical mechanism is to have an impact on the micro-market price by changing market relations from two-dimensional to three-dimensional. Its path to functioning at the macro level is to influence economic behaviors by changing the expectations of investment and consumption, resulting in new economic trends.